Punishing schools: fear and citizenship in American public education - Lyons, William (Law, meaning and violence, 2006)
Punishing schools and a zero tolerance culture -- Talking out of school : living and learning in suburbia -- Popular culture and public pedagogy : fear and identity in Suburbia and Pleasantville -- Punitive politics and punishing schools -- The place of urban high school in central city political culture -- Zero tolerance culture : fear as punishment, patronage, and pedagogy.